2021
DOI: 10.3390/healthcare9111533
|View full text |Cite
|
Sign up to set email alerts
|

An Observational Study Comparing Fibromyalgia and Chronic Low Back Pain in Somatosensory Sensitivity, Motor Function and Balance

Abstract: Fibromyalgia (FM) and chronic low back pain (CLBP) have shared pathophysiology and have a considerable impact on patients’ daily activities and quality of life. The main objective of this study was to compare pain impact, somatosensory sensitivity, motor functionality, and balance among 60 patients with FM, 60 patients with CLBP, and 60 pain-free controls aged between 30 and 65 years. It is essential to know the possible differences existing in symptomatology of two of the major chronic pain processes that mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Chronic pain and fatigue are the primary symptoms of FMS [23]. Previous research indicates that several populations, including those with neck pain, proprioceptive, and postural disturbances, are associated with pain and muscle fatigue [24,25]. In addition, different authors showed that proprioceptive retraining enhanced postural control [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic pain and fatigue are the primary symptoms of FMS [23]. Previous research indicates that several populations, including those with neck pain, proprioceptive, and postural disturbances, are associated with pain and muscle fatigue [24,25]. In addition, different authors showed that proprioceptive retraining enhanced postural control [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…The framework that defines motor dysfunction as a feature of FM syndrome has been initially supported by data showing that FM patients perform worse in clinical parameters of motor functionality than controls – as evidenced by worse motor and walking speed and other kinematics of gait and balance 33 – 36 . A recent experimental trial found FM to be even more severely impaired in these metrics than chronic low back pain subjects 37 . Moreover, this composition has been supported by neurophysiological data pointing to deficits specifically in psychomotor processing during motor control/inhibition tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Also, joint hypermobility is three times more frequent in fibromyalgia than in control groups [ 60 ]. And, importantly, upon specific proprioception testing in fibromyalgia cohorts, significant alterations have been demonstrated in muscle contraction [ 61 , 62 ], muscle relaxation [ 63 ], vibration perception [ 61 ], joint position sense [ 64 67 ], and the proprioceptive component of postural control [ 61 , 65 , 68 71 ] with frequent falls [ 68 , 72 , 73 ]. Problems in postural control or balance are also related to altered vestibular and visual dysfunction [ 68 , 73 , 74 ], which may indicate that sensory weakness is not limited to proprioception in fibromyalgia [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%